Flexible five-in-one micro sensor for in-situ diagnosis of high-temperature proton exchange membrane fuel cell stack. (7th December 2015) - Lee, Chi-Yuan; Weng, Fang-Bor; Chuang, Sheng-Ming; Lee, Shuo-Jen; Huang, Yen-Pu; Cheng, Yen-Ting; Cheng, Chih-Kai
Abstract: During the chemical reaction process of high-temperature proton exchange membrane fuel cell (HT-PEMFC) stack, the non-uniformity of internal local temperature, voltage, pressure, flow rate and current would result in poor membrane durability, fuel distribution non-uniformity and adverse impact on the fuel cell stack performance and service life. This study applies the micro-electromechanical systems (MEMS) technology to develop a flexible five-in-one micro sensor resistant to the high-temperature electrochemical environment. Six integrated micro sensors are embedded in the cathode field plate of HT-PEMFC stack. At the operational temperature of 160 °C, current (5, 13, 20 A) and long term testing results suggest that the trends of the curves of the internal local temperature, voltage, pressure, flow rate and current density of the fuel cell stack are considerably consistent, and the embedded flexible five-in-one micro sensors for in-situ diagnosis of fuel cell stack have impact of about 1.3% on fuel cell stack performance. The upstream temperature is higher than the downstream. The test result also shows that the heat distribution in the fuel cell stack is nonuniform. Highlights: To develop the flexible five-in-one micro sensor for in-situ diagnosis in a high-temperature proton exchange membrane fuel cell stack. The flexible micro sensors are: (1) small; (2) highly sensitive; (3) in situ measurement. Monitoring the distribution of the temperature, voltage, pressure, flow rate and current can stabilize fuel cell stack performance.